2020
DOI: 10.1111/trf.16086
|View full text |Cite
|
Sign up to set email alerts
|

Hemochromatosis alters the sensitivity of red blood cells to mechanical stress

Abstract: Background: Hemochromatosis (HH) is characterized by chronic iron accumulation, leading to deleterious effects to various organ systems. A common approach to managing iron load involves large-volume venesection. Some countries authorize HH venesections to be used in the development of transfusable blood products, although concerns remain regarding suitability. Due to the high oxidative load associated with hyperferritinemia, it has been proposed that HH blood products may be susceptible to mechanical damage. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…In blood units drawn form 19 HC patients, a significantly decreased deformability and increased shear stress were observed compared to controls, but there was no clear evidence that an acute exposure to elevated iron levels was the cause of the observed differences ( 43 ). An Australian study on 15 volunteers with HC and 11 controls confirmed these data, suggesting that blood products from HC individuals can be more prone to damage and that this can be exacerbated in situations of elevated shear stress (e.g., transfusion during surgery) ( 44 ). However, the same authors also reported on an improvement of the mechanical properties of red blood cells of HC individuals following iron removal treatment, indicating a possibly crucial role of elevated ferritin in plasma in determining the previously observed cellular changes ( 45 ).…”
Section: Short Review On Hc and Blood Donationmentioning
confidence: 85%
“…In blood units drawn form 19 HC patients, a significantly decreased deformability and increased shear stress were observed compared to controls, but there was no clear evidence that an acute exposure to elevated iron levels was the cause of the observed differences ( 43 ). An Australian study on 15 volunteers with HC and 11 controls confirmed these data, suggesting that blood products from HC individuals can be more prone to damage and that this can be exacerbated in situations of elevated shear stress (e.g., transfusion during surgery) ( 44 ). However, the same authors also reported on an improvement of the mechanical properties of red blood cells of HC individuals following iron removal treatment, indicating a possibly crucial role of elevated ferritin in plasma in determining the previously observed cellular changes ( 45 ).…”
Section: Short Review On Hc and Blood Donationmentioning
confidence: 85%
“…13 The extensional recovery time for healthy erythrocytes is approximately 100-130 ms 14 ; for blood loops employing a 5 L•min -1 flow rate the test volume would thus approximate 11 ml. Note that the extensional recovery time, recoverability of cell deformability, and cell shear modulus are sensitive to blood quality, 15,16 chemical rigidification, 17 level of shear exposure, 18 and disease states [19][20][21][22] ; thus, this minimum volume threshold represents the best case scenario; however, for pragmatic reasons (e.g., sampling volume requirements or HVAD fill volume of ~15 ml) is unlikely to be of value in the real world. Irrespective, the smallest blood loop in the present study (80 ml) was well above this estimated threshold, and given the agreement in hemolysis with the larger loops, provides encouraging data for those attempting to introduce human blood into preclinical medical device assessment.…”
Section: Discussionmentioning
confidence: 99%
“…13 The extensional recovery time for healthy erythrocytes is approximately 100–130 ms 14 ; for blood loops employing a 5 L·min -1 flow rate the test volume would thus approximate 11 ml. Note that the extensional recovery time, recoverability of cell deformability, and cell shear modulus are sensitive to blood quality, 15,16 chemical rigidification, 17 level of shear exposure, 18 and disease states 19–22 ; thus, this minimum volume threshold represents the best case scenario; however, for pragmatic reasons ( e.g. , sampling volume requirements or HVAD fill volume of ~15 ml) is unlikely to be of value in the real world.…”
Section: Discussionmentioning
confidence: 99%